The Politics of Counterterrorism in India : Strategic Intelligence and National Security in South Asia - Mahadevan, Prem. (2012)
Combining a theoretical approach with empirical analysis of India's counterterrorist activities, this book holds valuable information for those examining strategy-making and counterterrorism - practitioners as well as researchers - in addition to those interested in the politics of India.
Keywords: Terrorism -- India -- Prevention; Terrorism -- Prevention -- Government policy -- India; National security -- India